2012
DOI: 10.1111/j.1365-2095.2012.00972.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary protein and lipid levels on growth, feed utilization and body composition inPseudobagrus ussuriensisfingerlings

Abstract: An 8-week feeding trial was conducted to investigate the optimum dietary protein and lipid levels for growth, feed utilization and body composition of Pseudobagrus ussuriensis fingerlings (initial weight: 3.40 ± 0.01 g). Twelve diets containing four protein levels (350, 400, 450 and 500 g kg À1 crude protein) and three lipid levels (50, 100 and 150 g kg À1 crude lipid) were formulated. Fish were randomly allotted to 36 aquaria (1.0 9 0.5 9 0.8 m) with 25 fish to each glass aquarium. Fish were fed twice daily (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 24 publications
16
26
0
Order By: Relevance
“…However, in this study increasing dietary protein and lipid levels resulted in significant reduction of feed intake. This is in agreement with results of studies on channel catfish (Ictalurus punctatus) (Page and Andrews, 1973) and Pseudobagrus ussuriensis (Wang et al, 2013) where feed intake decreased with increasing protein and lipid levels. It has been generally suggested that fish like other animals, eat primarily to satisfy their energy requirements (Cho and Kaushik, 1985;Kaushik and Medale, 1994).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, in this study increasing dietary protein and lipid levels resulted in significant reduction of feed intake. This is in agreement with results of studies on channel catfish (Ictalurus punctatus) (Page and Andrews, 1973) and Pseudobagrus ussuriensis (Wang et al, 2013) where feed intake decreased with increasing protein and lipid levels. It has been generally suggested that fish like other animals, eat primarily to satisfy their energy requirements (Cho and Kaushik, 1985;Kaushik and Medale, 1994).…”
Section: Discussionsupporting
confidence: 92%
“…In the present study fish fed low-protein diets used dietary protein more efficiently, as higher PER values were recorded compared to those fed the high protein diets. Similar results have also been reported in other fish species (Deng et al, 2011;Mohseni et al, 2013;Wang et al, 2013). This could be explained by the existence of a compensatory mechanism enabling higher PER for fish fed low-protein diets (Berger and Halver, 1987;Catacutan et al, 2001).…”
Section: Discussionsupporting
confidence: 87%
“…() and Wang et al. (), as well as an increased whole‐body lipid deposit, supporting the findings of Siddiqui and Khan () due to deamination and storage as body fat of excess dietary protein, accompanied by a reduction in whole‐body moisture and ash. It appears that the increases in whole‐body protein and lipid deposits were at the expense of moisture and ash deposits with the increase in dietary protein levels.…”
Section: Discussionsupporting
confidence: 74%
“…As the largest one of bagrid catfish species, it has been recently added into aquaculture in China because of its delicious meal and better production performance (Ou et al 2014;Wang et al 2013b). Field surveys and aquaculture practices have observed significant sexual dimorphism in growth rate and body size, in which males grow faster than females, and result in an ultimate threefold size difference.…”
Section: Introductionmentioning
confidence: 99%